2000
DOI: 10.1590/s0034-89102000000200004
|View full text |Cite
|
Sign up to set email alerts
|

Comparação entre a colpocitologia oncológica de encaminhamento e a da gravidade das lesões cervicais intra-epiteliais

Abstract: Comparação entre a colpocitologia oncológica de encaminhamento e a da gravidade das lesões cervicais intra-epiteliais Oncologic colpocytology collected in the public health and reference services in the diagnostic of the severity of intraepithelial cervical lesion

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
14

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 8 publications
1
5
0
14
Order By: Relevance
“…Nevertheless, approximately one third of the cases identified by RR-100% on previous cytopathology were found to be normal at colposcopy. These results are similar to those reported by Lapin et al [24], who detected abnormalities at colposcopy in 70.9% of cases that had tested abnormal on previous cytopathology. The frequency of confirmed results in the study conducted by Katz et al [25] was higher (95.6%); however, agreement was poor between cytopathology and colposcopy.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Nevertheless, approximately one third of the cases identified by RR-100% on previous cytopathology were found to be normal at colposcopy. These results are similar to those reported by Lapin et al [24], who detected abnormalities at colposcopy in 70.9% of cases that had tested abnormal on previous cytopathology. The frequency of confirmed results in the study conducted by Katz et al [25] was higher (95.6%); however, agreement was poor between cytopathology and colposcopy.…”
Section: Discussionsupporting
confidence: 92%
“…These results are in agreement with findings from studies that evaluated the performance of cytopathology using histopathology as the gold standard. In these studies, the frequency of results confirmed by histopathology ranged from 62.8 to 86.6% [24,25,31,32,33]. Sensitivity ranged from 51.0 to 91.6% [33,34,35,36,37,38,39,40,41,42,43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Estas estão relacionadas à amostra celular insuficiente, preparação inadequada dos esfregaços, leitura errada das lâminas, ausência de controle de qualidade dos laboratórios de citopatologia, interpretação inadequada dos achados citológicos e segmento inadequado das mulheres com esfregaços alterados (LAPIN; DER-CHAIN; TAMBASCIA, 2000).…”
Section: Introductionunclassified
“…De acordo com os dados informados, é possivel dizer que a citologia, de forma isolada, é considerada como um método limitado (11); porém a associação entre citologia, colposcopia e histologia no diagnóstico das lesões intraepiteliais e carcinoma é essencial para uma conduta adequada tanto para a prevenção quanto para o tratamento das lesões (12).…”
Section: Introductionunclassified